The role of the body in the foundation of the conscious mind and proprioception:: channels of bodily information and their roles in the constitution of bodily self-awareness - Almada, Leonardo Ferreira; Romão, Fabiense Pereira (Sofia, 2023)
The problem we will focus on in this paper is the following: in light of the resources we have in philosophy of mind, and based on what we know about phylogeny and ontogeny, is it possible to support the body as the fundamental basis for the constitution of consciousness? If yes, in what sense? Based on a theoretical, structural, theoretical and methodological source provided by neuroscientists and philosophers of mind dedicated to the embodied approach to the mind, we will dedicate ourselves to supporting some reflections on the idea of the body as the foundation of the mind, and notions such as self-awareness and proprioception in the constitution of bodily self-awareness. Our purpose is to delimit some bases of our naturalistic and non-reductive position on the mind.